Differential Patterns of Food Appreciation during Consumption of a Simple Food in Congenitally Anosmic Individuals: An Explorative Study - Novakova, Lenka; Bojanowski, Viola; Havlíček, Jan; Croy, Ilona (PLOS ONE, 2012)
Food is evaluated for various attributes. One of the key food evaluation domains is hedonicity. As food is consumed, its hedonic valence decreases (due to prolonged sensory stimulation) and hedonic habituation results. The aim of the present study was to investigate changes in food pleasantness ratings during consumption of a simple food by individuals without olfactory experience with food as compared to normosmics. 15 congenital anosmics and 15 normosmic controls were each presented with ten 10 g banana slices. Each was visually inspected, then smelled and chewed for ten seconds and subsequently rated for hedonicity on a 21-point scale. There was a significant difference in pleasantness ratings between congenital anosmics and controls (F(1, 26) = 6.71, p = .02) with the anosmics exhibiting higher ratings than the controls, a significant main repeated-measures effect on the ratings (F(1.85, 48) = 12.15, p<.001), which showed a decreasing trend over the course of consumption, as well as a significant portion*group interaction (F(1.85, 48) = 3.54, p = .04), with the anosmic participants experiencing a less pronounced decline. The results of the present explorative study suggest that over the course of consumption of a simple food, congenitally anosmic individuals experience differential patterns of appreciation of food as compared to normosmics. In this particular case, the decrease of hedonic valence was less pronounced in congenital anosmics.